Asynchronous variation in the holocene asian monsoon recorded by marine sediments and its implication - Yang, Jun; Zhang, Guanglu; Zhao, Yanyan; Zhang, Zhishun; Liu, Sheng; Wei, Haotian; Guo, Xiaoqiang; Cao, Guangyao; Yang, Lei; Zhang, Yaru; Li, Sanzhong (Frontiers in Earth Science, 2025)
The long-term evolution of climate during the Holocene remains controversial, as proxy and model data, and multiple proxies, show diverging temperature trends between the different reconstructions. Here, we compile sea surface temperature (SST) from multiple marine sediment records in the South China Sea (SCS) and Indo-Pacific over the Holocene, which reveal a phase difference in the precession band of different marine sediment records. Peak identification was performed on the data from each site, and the sea surface temperature anomalies (SSTA) was simply divided into two modes, the Early Holocene (EH-peak) and Middle Holocene (MH-peak), based on the timing of the first maximum peak, using 9 ka as the boundary. The phase difference between the two modes is ∼3 ka in the precession band. We suggest that the phase difference corresponds to the shifts in the mean latitudinal position of the Intertropical Convergence Zone (ITCZ) driven by the Northern Hemisphere Summer Insolation (NHSI). Two modes indicate the warming of the SSTA during the late Holocene, which may be attributed to rising pCO2, a strengthening El Niño, and a weakening of the East Asian winter monsoon (EAWM). Furthermore, we observe a partial overlap between the site distribution of the MH-peak and the modern monsoon precipitation domains, which may indicate the shift in the mean latitudinal position of the ITCZ and the dynamics of the monsoon precipitation domains.